Influence of the First Thousand Days of Life on Stunting Incidence - Linda Meliati; Sudarmi Sudarmi; St Halimatusyaadiah (Journal of Holistic Nursing and Midwifery)
Introduction: The golden period is the first 1000 days of a child's life. Stunting is one of the consequences of long-term malnutrition occurring in the first two years of a child's life. Stunting is widely known as a condition of failure in a child's growth so that the child becomes short or shorter than average for his age and experiences delays in cognitive development. Objective: This study aimed to analyze the effect of the first 1000 days of life (1000 HPK) as a risk factor for stunting in West Nusa Tenggara Province, Indonesia, in 2018. Materials and Methods:  This study was an analytical observational study with a cross-sectional design that was conducted from March to July 2022. The study population included all toddlers aged 0-59 months, as recorded in the 2018 Riskesdas survey in West Nusa Tenggara Province, Indonesia. A total sample of 1119 toddlers met the inclusion criteria. The data used were secondary data obtained from the Data and Information Agency for Health Development Policy, Ministry of the Republic of Indonesia (datin.bkppk@kkemkes.go.id). The collected data were sorted out using descriptive statistical analysis (frequency distribution) and analyzed by bivariate analysis with the Chi-square test. Moreover, we used multivariate analysis using the logistic regression test. Results: Most toddlers aged 0–59 months did not experience stunting (72.7%). The mothers data were as follows: majority of mothers were too young ≥ 20 years (66.7%) or too old ≤ 35 years (99.2%), with pregnancy interval ≥ 2 years (71.6%), and number of living children ≤ 2 (71.1%), antenatal care (99.7%), hemoglobin examination (87%), and consumed ≥ 90 iron tablets (62.4%). Also, 50.8% of mothers did not breastfeed their children. The variables of pregnancy interval (P = 0.047), number of living children (P = 0.039), and breastfeeding (P = 0.0001) affected stunting. At the same time, the mother's age (too young or too old), antenatal care, provision of iron tablets, and hemoglobin examination had no effect. The dominant factor influencing stunting is breastfeeding (odds ratio = 2.063; 95% CI, 1.590 – 2.740; P = 0.0001). Conclusion: Breastfeeding is the most dominant variable affecting the incidence of stunting.